Justice in the Administration and Settlement of Bankruptcy Estate by Auction in Relation to the Recovery of Creditors’ Claims - Ricki Rahmad Aulia Nasution; Iwan Erar Joesoef; Heru Sugiyono (International Journal of Law and Society, 2025)
This study aims to examine the aspect of justice in the administration and settlement of bankrupt assets by the Curator, particularly concerning the repayment of receivables to creditors in the context of auction minutes issued by the KPKNL Samarinda. The research adopts a normative juridical method, legislation approach and conceptual approach, and is connected to a case study approach focusing on the auction process in the bankruptcy case of PT Karebet Mas Indonesia (in bankruptcy). The results of this study indicate that the Curator, in administering and settling unsold bankrupt assets, may proceed with a private sale (underhand sale) with the approval of the supervising judge, based on a limit value obtained from an independent appraiser’s valuation, provided that at least two public auctions have been conducted without success. The distribution of assets to creditors must observe the principle of pari passu pro rata, which ensures equal treatment according to their respective priorities.In the event that the settlement process of the bankrupt estate has been declared completed, yet the creditors have not received full repayment of their claims, the general provisions under Article 1131 of the Indonesian Civil Code shall apply, namely that all of the debtor’s assets constitute collateral for the fulfillment of their debts. This study recommends an amendment to Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, to regulate in a detailed, specific, and comprehensive manner the requirements for the underhand sale of bankrupt assets by the Curator. Such regulation is necessary to ensure justice and legal certainty for bankrupt debtors and creditors, particularly regarding the repayment of claims for concurrent creditors.